Overcoming Bereavement in Sigrid Nunez's The Friend (2018) - Agustiliana, Sherly; Anwar, Desvalini (Universitas Negeri Padang, 2023)
The purpose of this analysis is to expose the issue of overcoming bereavement in the novel The Friend (2018) by Sigrid Nunez. This analysis discusses the effects that occurs to the main character after losing someone she loves and the ways she does to overcome the bereavement. The conflict that occurs to the main character is losing someone she loves because of suicide and makes her feeling devastated and difficult for her to live, but she soon gets up from this loss thus, she can return to living her life as before. This analysis is related to the concept of defense mechanism which proposed by Sigmund Freud. The use of the concept is based on the interpretation of text and context of the novel. Also, uses a lot of fictional element such as theme, plot, and character to reveal the meaning. The result of the study shows that losing someone she loves effects her life but she also show her ways to overcome the bereavement she had and continue her life.